Sociodemographic Factors Influencing Vietnamese Patient Satisfaction with Healthcare Services and Some Meaningful Empirical Thresholds - Quan-Hoang VUONG (Tehran University of Medical Sciences, 2017)
Background: This short communication report some new results obtained from a medical survey among 900 Vietnamese patients in 2015, looking into possibly influential sociodemographic factors as far as patient satisfaction is concerned, to establish empirical relationships between them for policy implications. Methods: The study employed the baseline category logit models to establish empirical relationships between predictor variables and responses, which reflect different levels of satisfaction. Results: Income, medical expenditure, and insurance coverage have the positive influence on improving patient satisfaction. However, insurance reimbursement rate has the negative influence. Patients with residency status are more demanding than those without. The more seriously ill, the less likely a patient finds the health services to be satisfactory. The probability of satisfaction conditional on insurance reimbursement is lower for patients with residency status, and higher for those without. Conclusion: There exist thresholds of income, expenditures, and insurance reimbursement rate, surpassing which probabilistic trends shift. The expenditure threshold for resident patients is almost three times of that for non-residents. An insurance threshold exists only within the group of non-resident patients, ~65%, suggesting that getting a reimbursement rate higher than this can be very difficult. Therefore, the government's ambitious goal of universal coverage may be both unrealistic and too rigid as patients with different conditions show different perceptions toward healthcare services.